ANALISIS PERLAKUAN AKUNTANSI PAJAK PERTAMBAHAN NILAI (PPN) PADA CV. MULTI DI KOTA MANADO - Tangkere, Marcho Rivelino; Elim, Inggriani; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Lease represent one of the very potential acceptance and dominant enough because owning function of budgetair and arrange. Taxation which in it there are element of Value Added Tax (PPN) represent also the part of fiscal policy of government because one of the Iease type imposed by government is Value added tax (PPN). As for intention of this research is to know treatment of Value added tax accountancy conducted by CV. Multi. Pursuant to result of research, hence Applying of Value added tax cv. Multi have according to Law No. 42 year 2009. Treatment of Value added tax accountancy by cv. Multi as entrepreneur hit Iease have as according to Law No. 42 Year 2009 that is equal to 10% for the delivery of home affairs.